Analisis Tingkat Pemahaman Mahasiswa Fisika Universitas Jember Tentang Mekanisme Pembangkit Listrik Tenaga Sampah ( PLTSa ) - Adinda Nina Eka Sakti; Sudarti, Sudarti; Yushardi, Yushardi (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
Waste is a factor that causes various kinds of problems in the surrounding environment, especially in Indonesia. The lack of public awareness causes  garbage that accumulates everywhere to manage the waste properly. Over time, the accumulation of waste can have a detrimental impact, ranging from health problems and environmental damage to the economic sector. Therefore, this study aims to analyze aspects of knowledge and aspects of understanding of Jember University Physics students regarding the  mechanism of waste power plants (PLTSD). This research was conducted using quantitative methods with a descriptive approach through questionnaires through google forms on 50 students. Based on the analysis that has been carried out, it was obtained that the level of understanding of Physics Students at the University of Jember is the mechanism of waste power generation in terms of the understanding aspect and the understanding aspect is quite good. It is evident from the percentage results obtained on each questionnaire question more than 50% of students already understand the mechanism of waste power plants in utilizing waste as an alternative energy source.